One-year clinical outcome of biodegradable polymer sirolimus-eluting stent in patients needing short dual antiplatelet therapy. Insight from the ULISSE registry (ULtimaster Italian multicenter all comerS Stent rEgistry). (1st September 2019) - Godino, Cosmo; Beneduce, Alessandro; Ferrante, Giuseppe; Ielasi, Alfonso; Pivato, Carlo Andrea; Chiarito, Mauro; Cappelletti, Alberto; Perfetti, Giulia; Magni, Valeria; Prati, Eugenio; Falcone, Stefania; Pierri, Adele; et al.
Abstract: Background: This study aimed to evaluate real-world clinical outcome of patients needing short dual antiplatelet therapy (S-DAPT) following PCI with Ultimaster® thin-strut, biodegradable polymer sirolimus-eluting stent (BP-SES), which was supposed to induce faster stent endothelialization and reduce device thrombogenicity. Methods: In this sub-group analysis of patients enrolled in the ULISSE registry, two groups were identified: 1) patients discharged with S-DAPT (≤3-month) due to high bleeding risk or need for urgent major non-cardiac surgery and 2) patients discharged with recommended DAPT (R-DAPT) duration (≥6-month). The primary ischemic-safety and bleeding-safety endpoints were TLF (composite of cardiac-death, target vessel MI, and clinically driven target lesion revascularization), and BARC major bleedings (≥type-3a) at 1-year follow-up. To account for events occurring before DAPT discontinuation we performed 3-month landmark analysis. Results: 82 patients (5%) were discharged with ≤3-month DAPT (57 ± 27 days), and 1558 patients (94%) were discharged with ≥6-month DAPT (318 ± 75 days). No significant differences between S-DAPT and R-DAPT group were observed in TLF at 1-year (7.9% vs. 4.6%). The rate of BARC major bleeding resulted significantly higher in S-DAPT group (3.9% vs. 0.3%; p = 0.001), with the majority of bleeding events occurring within 3 months. The landmark analysis showed no significant differences in BARC major bleedings between groups (1.4% vs. 0.3%; p = 0.142). Conclusions: As compared to those treated with R-DAPT (≥6-month), patients needing -S-DAPT (≤3-month) after PCI with Ultimaster® BP-SES had similar rates of 1-year TLF and BARC major bleedings following early DAPT discontinuation. Highlights: S-DAPT and R-DAPT after PCI with Ultimaster® BP-SES resulted in similar 1-year TLF. S-DAPT group had higher bleeding risk and significantly higher BARC major bleedings. Landmark analysis at 3-month showed similar BARC major bleedings between the groups.